ALIH KODE DAN CAMPUR KODE DALAM KOMUNITAS MAHASISWA PERANTAUAN ACEH DI YOGYAKARTA - Cut Irna Liyana (Jurnal Community, 2017)
The aims of this study are to describe and explain the form of code switching and code mixing, to identify the factors of code switching and code mix and to identify the purpose and function of code switching and code mixing in the Acehnese students in Yogyakarta. This is descriptive qualitative research by sociolinguistic approach. The method used in this research is observation method and record technique. The data of this research are the speechs of Acehnese students who are studying in Yogyakarta which contains of code switching and code mixing. Data were identified and classified and then analyzed by existing sociolinguistic theory.The results show that: first, the form of code transfer in Acehnese student communication in Yogyakarta includes the switch of code from Acehnese Language to Indonesian and the switch of code from Indonesian to Aceh; second, the form of mixed code in the form of insertion of words, phrases, and clauses; third, the factors of code switching and code mixing are speakers, participants, third speakers, speech mode and discussion topics; fourth, the purpose and function of code switching and code mixing in the Acehnese students are to familiarize the situation, to make a sense of humor, to look prestigious, to respect the other person and to tell the secret.Key words        : Code Switching, Code Mixing, Sociolinguistic